In-wheel, outer rotor, permanent magnet synchronous motor design with improved torque density for electric vehicle applications - Mustafa Yaseen Bdewi; Mohammed Moanes Ezzaldean Ali; Ahmed Mahmood Mohammed (International Journal of Electrical and Computer Engineering (IJECE), 2022)
In electric vehicle applications, the torque density of electric motor plays an important role in improving the performance of the vehicle. The main objective of this paper is to investigate a possible method for improving the torque density of a permanent magnet synchronous motor used in electric vehicles. At the same time, other machine specifications were taken into account and kept within the acceptable level. This was achieved by incorporating performance enhancement strategies such as investigating ofhigh-efficient winding topology for the motor’s stator to give the highest winding factor and optimizing the machine dimensions to achieve the best performance. MagNet 7.4.1 software package with static and transient finite element method solver was used for implementing the proposed design. The results showed a significant improvement in the torque density with keeping the overall machine performance.